Secular Tolerance? Anti‐Muslim Sentiment in Western Europe. Issue 2 (10th August 2017) - Ribberink, Egbert; Achterberg, Peter; Houtman, Dick
Abstract : The literature about secularization proposes two distinct explanations of anti‐Muslim sentiment in secularized societies. The first theory understands it in terms of religious competition between Muslims and the remaining minority of orthodox Protestants; the second understands it as resulting from value conflicts between Muslims and the nonreligious majority. The two theories are tested by means of a multilevel analysis of the European Values Study 2008. Our findings indicate that, although more secularized countries are on average more tolerant towards Muslims and Islam, strongest anti‐Muslim attitudes are nonetheless found among the nonreligious in these countries.